Quality Characteristics of Yogurt Added with Karamunting (Rhodomyrtus tomentosa) Aqueous Extract As Natural Colorant and Source of Antioxidant. (Jurnal Ilmu dan Teknologi Hasil Ternak, 2022)
The aims of this research are to determine the effect of the concentration addition level of karamunting (Rhodomyrtus tomentosa) fruit extract on the quality of yogurt during 9 d storage period to increase the functionality of yogurt as a probiotic food, a source of antioxidants and the use of karamunting as a natural colorant for food. This research used a completely randomized design consisting of two factors, that is the concentration of karamunting fruit extract which consisted of 4 addition levels (0%, 12%, 15% and 18% w/w) and the storage period of yogurt which also consisted of 4 levels (0 d, 3 ds, 6 d and 9 ds). The parameters that have been observed in this research were pH, total acid, water content, fat content, protein content, color analysis, antioxidant activity and organoleptic tests (aroma, taste, viscosity and color) of the yogurt. The results showed that karamunting fruit extract had a significant effect on pH, total acid, color L*, a* and b*, and organoleptic (aroma, viscosity and color) of the yogurt, but had no significant effect on water content, fat content, protein content and flavor of the yogurt. Storage period had a significant effect on pH, total acid, protein content, color L*, a* and b*, and organoleptic (aroma, taste, viscosity and color) of the yogurt, but had no significant effect on water content and fat content of the yogurt. The addition of 18% (w/w) karamunting fruit extract and 9 d of storage period resulted in yogurt with the characteristics as follows pH 4.2; total acid 1.57%; water content 87.05%; fat content 3.66%; protein content 2.7%; color L* 72,24; a* 8.28; and b* 9.38 and organoleptic (aroma, taste, thickness and color) which were quite favorable, as well as a strong antioxidant activity value of 85.35 ppm IC50.